CULTURALLY RESPONSIVE MATHEMATICS PEDAGOGY: INSIGHTS FROM NCF-2023 AND ETHNOMATHEMATICS - Howlader, Mampi; Sarkar, Puja (STKIP PGRI Tulungagung, 2025)
Throughout the school curriculum, mathematics is an indispensable subject that is used in both everyday life and the study of other disci-plines. Nonetheless, there is a widespread belief that most students despise mathematics. Numerous studies have shown that rather than the topic itself, the issue may be in the methods teachers use to teach. Only 43% of grade 8 students can answer grade 5 math problems, and only 28% of fifth-grade students can do division operations, according to the 2018 Annual Status of Education Report (ASER). To counter this problem, NCF-2023 suggests reassessing the pedagogical approach to foster students' interest in mathematics and integrate it into their daily lives. The purpose of our study is to teach various concepts of school mathematics through traditional activities. This study is descriptive in nature. We delimit our study to the foundational stage, the preparatory stage, and the middle stage. Furthermore, we only focus our study on Indian students and NCERT textbooks. We show how to teach the con-cept of the highest common factor (HCF), fractions, integers, and vari-ous shapes through the traditional activities of beading, pottery, weav-ing, and fishing.